Prevalence and predictors of gestational diabetes mellitus: a nationwide multicentre prospective study - ÜSTAY, ÖZLEM (WILEY, 2019)
Aim Prevalence rates of gestational diabetes mellitus (GDM) show considerable variation among different countries and regions of the world. The primary aim of this study was to determine the nationwide prevalence and predictors of GDM in Turkey. Methods We conducted prospective nationwide screening among pregnant women. Between August 2016 and November 2017, a total of 2643 pregnant women from 51 centres in 12 different regions were enrolled. A two-step screening method and Carpenter and Coustan criteria were used in the diagnosis of GDM. Clinical and biochemical data were obtained using electronic database software. Results The national prevalence of GDM was found to be 16.2% [95% confidence intervals (CI) 15.0% to 17.4%] without a significant difference between urban and rural regions. Women with GDM were older (mean age: 32 +/- 5 vs. 28 +/- 5 years, P < 0.001) and heavier (mean BMI: 27.2 +/- 5.1 vs. 24.7 +/- 4.7 kg/m(2), P < 0.001) than their counterparts without GDM. The prevalence of GDM tended to increase with age (< 25 years, 6.9%; 26-35 years, 15.6%; and 36-45 years, 32.7%; P < 0.001). Maternal age, maternal BMI, history of previous GDM and family history of diabetes mellitus were independent predictors of developing GDM (P < 0.05 for all). Low-risk women (age < 25 years, BMI < 25 kg/m(2), no family history of diabetes) comprised 10.7% of the total population and the prevalence of GDM in these women was 4.5% (95% CI 2.4% to 7.8%). Conclusion The results of this nationwide study indicate that GDM is very common, affecting one in seven pregnancies in Turkey. Implementation of international guidelines on screening and management of this public health problem is required.
Keywords: RISK-FACTORS; PREGNANCY; WOMEN; EPIDEMIOLOGY; ASSOCIATION; CRITERIA; TURKEY